The impacts of feed fraction on copolymer microstructure in ATRcP: a kinetic Monte Carlo simulation. (3rd April 2019) - Serajian, Sahand; Najafi, Mohammad; Amiri, Anahita
Abstract: A research has been carried out to simulate an atom transfer radical copolymerization (ATRcP) system of styrene and n -butyl acrylate using the stochastic Monte Carlo method and to investigate the variation of reactant concentration, average molecular weight and molecular weight distribution, average sequence length and sequence length distribution, different dyad fractions and copolymer composition as a function of styrene feed fraction. To this end, a finely tuned program was written in C++ language to implement the simulation algorithm. It was observed that although styrene feed fraction alteration affected all the factors under review, weight-average molecular weight showed the least variation in its trend for styrene fractions higher than 5%. Finally, the outputs of the current work can be effectively used in tuning and controlling the topology and microstructure of copolymer chains. Abstract :